2009
DOI: 10.2340/16501977-0340
|View full text |Cite
|
Sign up to set email alerts
|

Inactive lifestyle in adults with bilateral spastic cerebral palsy

Abstract: Adults with bilateral spastic cerebral palsy, especially those with low-level gross motor functioning, are at risk for an inactive lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
79
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 37 publications
12
79
0
1
Order By: Relevance
“…However, similar findings have been previously reported for people with physical and sensory disabilities (including visual impairment) and adults with intellectual disability or cerebral palsy (Holbrook et al, 2009;Longmuir & Bar-Or, 2000;Nieuwenhuijsen et al, 2009;Stanish et al, 2006). It seems that the presence of some disabilities limits the participants' physical activity and attenuates gender disparities that are frequently found in general population surveys.…”
Section: Counts Per Min)supporting
confidence: 77%
“…However, similar findings have been previously reported for people with physical and sensory disabilities (including visual impairment) and adults with intellectual disability or cerebral palsy (Holbrook et al, 2009;Longmuir & Bar-Or, 2000;Nieuwenhuijsen et al, 2009;Stanish et al, 2006). It seems that the presence of some disabilities limits the participants' physical activity and attenuates gender disparities that are frequently found in general population surveys.…”
Section: Counts Per Min)supporting
confidence: 77%
“…However, the conflicting evidence regarding the use of accelerometry to estimate PA in nonambulatory adult wheelchair users warrants the need for further investigation in this population (15,40). Furthermore, the use of wrist-worn accelerometers in adolescents and adults with CP has been limited (23). Past literature has also emphasized the importance of implementing population specific cut points to properly interpret accelerometry activity output (41).…”
mentioning
confidence: 96%
“…Individuals with CP have been reported to be less physically active than their able-bodied peers (19,23,37). This reduction in physical activity (PA) is a concern as it has been well established that PA in healthy children and adults decreases the risk of cardiovascular health disease and other secondary health concerns (1,30).…”
mentioning
confidence: 99%
“…However, some work physiology concerning this particular field of rehabilitation has survived because these studies provided insights into the improvement of residual function (i.e., aerobic fitness) in children or athletes with cerebral palsy rather than the recovery of lost function 3,10,[25][26][27][28] . However, only a few recent studies by researchers like Nieuwenhuijsen et al 55,56) and Satonaka, et al [19][20][21][22] have reported on nonathletic adults with cerebral palsy rated to GMFCS level III or IV. Somehow, the fitness levels of this population are neglected after they complete their childhood rehabilitation programs 57) .…”
Section: History Of Research On Aerobic Fitness In Individuals With Cmentioning
confidence: 99%
“…This has been attributed to lower physical activity levels in the former population 25,37) . This trend of less physical activity may begin after completion of childhood rehabilitation programs or leaving school 55,57) . Individuals with cerebral palsy often have difficulty in finding jobs, and their physical activity and aerobic fitness levels may decline in adulthood.…”
Section: Aerobic Fitness May Be Improved By Physical Activity Other Tmentioning
confidence: 99%